1980
DOI: 10.1159/000467255
|View full text |Cite
|
Sign up to set email alerts
|

Some Notes on the Specificity of Anti-A^1 Reagents

Abstract: The agglutinability of red blood cells of A(1), A(2), A(3), A(x) and cis-AB phenotypes by several anti-A(1) reagents was quantitatively evaluated and found to correlate with the number of A antigenic sites/cell determined by using 125 I-labelled IgG anti-A. Moreover, anti-A(1) sera could be absorbed by some A(2) red blood cells and were inhibited by concentrated saliva from A(2) secretor individuals. The significance of these findings is discussed in the light of recent data from the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Apart from its agglutination properties, we observed weak reactivity toward A 2 test cells. This is known to be a weak interaction, which has been observed for anti‐A 1 agglutinins in serum . Our investigation of the anti‐A 1 specificity was conducted in the 56°C eluates revealing weak direct agglutination of A 2 RBCs at RT only and identical reaction patterns of the pre‐ and posttransfusion eluate.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Apart from its agglutination properties, we observed weak reactivity toward A 2 test cells. This is known to be a weak interaction, which has been observed for anti‐A 1 agglutinins in serum . Our investigation of the anti‐A 1 specificity was conducted in the 56°C eluates revealing weak direct agglutination of A 2 RBCs at RT only and identical reaction patterns of the pre‐ and posttransfusion eluate.…”
Section: Discussionmentioning
confidence: 85%
“…This is known to be a weak interaction, which has been observed for anti-A 1 agglutinins in serum. 16 Our investigation of the anti-A 1 specificity was conducted in the 568C eluates revealing weak direct agglutination of A 2 RBCs at RT only and identical reaction patterns of the pre-and posttransfusion eluate. The same holds for the pre-and posttransfusion DATs (both weakly positive), in which slightly stronger reactivity was observed in the posttransfusion sample likely due to residual transfused A 1 RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…9 Approximately 75-95% of blood group antigen determinants are bound to protein backbone structures, with the remaining antigen expressed on lipid backbones. 9,12 The nature of the mechanism underlying the difference between A 1 and A 2 erythrocytes has been a controversy for decades, with the literature divided among studies promoting a qualitative mechanism, 13-18 studies demonstrating a quantitative mechanism, [19][20][21][22] or studies advocating for both qualitative and quantitative differences. 23 It has been prominently reported that group A 2 erythrocytes express approximately 75% less A antigen on their surface relative to A 1 erythrocytes.…”
Section: Introductionmentioning
confidence: 99%